Immobilization of Lead and Nickel Ions from Polluted Yam Peels Biomass Using Cement-Based Solidification/Stabilization Technique - Ángel Villabona-Ortiz; Candelaria Tejada-Tovar; Ángel Gonzalez-Delgado; Adriana Herrera-Barros; Gina Cantillo-Arroyo (International Journal of Chemical Engineering)
Nowadays, biomass has been employed to prepare biosorbents for heavy metals uptake; however, further disposal of polluted material has limited its application. In this work, nickel and lead removal was performed using yam peels and the resulting polluted biomass was mixed with concrete to produce bricks. The biomass was characterized by FT-IR analysis for testing functional groups diversification before and after adsorption process. The effect of adsorbent dosage, temperature, and initial solution concentration was evaluated to select suitable values of these parameters. Adsorption results were adjusted to kinetic and isotherm models to determine adsorption mechanism. Desorption experiments were also performed to determine the appropriate desorbing agent as well as its concentration. Immobilization technique of cement-based solidification/stabilization was applied and the polluted biomass was incorporated to concrete bricks at 5 and 10%. Mechanical resistance and leaching tests were carried out to analyze the suitability of heavy metals immobilization. The suitable values for dosage, temperature, and initial solution concentration were 0.5 g/L, 40°C and 100 ppm, respectively. The kinetic model that best fitted experimental results was pseudo-second order indicating a dominant physicochemical interaction between the two phases. The highest desorption yields were found in 52.47 and 74.84% for nickel and lead ions. The concrete bricks exhibited compression resistance above 5 MPa and all the leachate reported concentrations below the environmental limit. These results suggested that nickel and lead immobilization using concrete bricks is a good alternative to meet disposal problems of contaminated biomass.